Tracking Object-State Representations During Real-Time Language Comprehension by Native and Non-native Speakers of English - Kang, Xin; Ge, Haoyan (Frontiers in Psychology, 2022)
The present ‘visual world’ eye-tracking study examined the time-course of how native and non-native speakers keep track of implied object-state representations during real-time language processing. Fifty-two native speakers of English and forty-six non-native speakers with advanced English proficiency joined this study. They heard short stories describing a target object (e.g., an onion) either having undergone a substantial change-of-state (e.g., chop the onion) or a minimal change-of-state (e.g., weigh the onion) while their eye movements towards competing object-states (e.g., a chopped onion vs. an intact onion) and two unrelated distractors were tracked. We found that both groups successfully directed their visual attention towards the end-state of the target object that was implied in the linguistic context. However, neither group showed anticipatory eye movements towards the implied object-state when hearing the critical verb (e.g., “weigh/chop”). Only native English speakers but not non-native speakers showed a bias in visual attention during the determiner (“the”) before the noun (e.g., “onion”). Our results suggested that although native and non-native speakers of English largely overlapped in their time-courses of keeping track of object-state representations during real-time language comprehension, non-native speakers showed a short delay in updating the implied object-state representations.